2020
DOI: 10.1039/c9ra08101a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-coated narrow groove plasmonic nanogratings for highly sensitive hydrogen sensing

Abstract: In this paper, we propose novel plasmonic hydrogen sensors based on palladium coated narrow-groove plasmonic nanogratings for sensing of hydrogen gas at visible and near-infrared wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Nanoparticles (NPs), such as those of platinum (Pt), palladium (Pd), ,, and Au–Pd, have attracted considerable interest for use in a variety of H 2 -sensing platforms and applications due to their unique catalytic abilities. Our basis for choosing Au–Pd NPs for our research objectives stems from reports describing how alloys containing Au and Pd are particularly advantageous for H 2 -sensing and exhibiting enhanced H 2 adsorption and solubility. , With respect to signal transduction for H 2 -sensing, catalytic NPs have been combined with different indicators for the development of optical H 2 sensors in which the sensing mechanism relies on the dissociation of H 2 at the NP surface to form highly reactive hydrogen atoms that subsequently undergo a redox reaction with an indicator to cause a visual color change. , For example, Seo et al used a reagent containing methylene blue and Pt NPs to quantify the amount of H 2 dissolved in water as the reagent underwent a blue to colorless transition upon reaction with H 2 .…”
mentioning
confidence: 99%
“…Nanoparticles (NPs), such as those of platinum (Pt), palladium (Pd), ,, and Au–Pd, have attracted considerable interest for use in a variety of H 2 -sensing platforms and applications due to their unique catalytic abilities. Our basis for choosing Au–Pd NPs for our research objectives stems from reports describing how alloys containing Au and Pd are particularly advantageous for H 2 -sensing and exhibiting enhanced H 2 adsorption and solubility. , With respect to signal transduction for H 2 -sensing, catalytic NPs have been combined with different indicators for the development of optical H 2 sensors in which the sensing mechanism relies on the dissociation of H 2 at the NP surface to form highly reactive hydrogen atoms that subsequently undergo a redox reaction with an indicator to cause a visual color change. , For example, Seo et al used a reagent containing methylene blue and Pt NPs to quantify the amount of H 2 dissolved in water as the reagent underwent a blue to colorless transition upon reaction with H 2 .…”
mentioning
confidence: 99%
“…They further calculated the hydrogen sensing performances of the Pd‐coated Au nanogratings and the Δλ was estimated to be ≈80 nm for PdH x = 0.65 . [ 86 ]…”
Section: Discussionmentioning
confidence: 99%
“…They further calculated the hydrogen sensing performances of the Pd-coated Au nanogratings and the Δλ was estimated to be ≈80 nm for PdH x = 0.65 . [86] The MIM configuration has been widely studied in experiments. A Pd/Y (WO 3 )/Au MIM configuration was investigated by Beni et al (Figure 10a,b), and a fast response time of 10 s (Figure 10c) was reported.…”
Section: Indirect Hydrogen Detection Based On Plasmonic Filmsmentioning
confidence: 99%
“…A high-performance plasmonic transmission structure consisting of two cascaded ultrathin metallic nanogratings was proposed, which obtained near-perfect transmission and ultra-narrow bandwidth of 20 nm in sensing and filtering applications [17]. A palladium-coated narrow groove nanograting was designed, which was able to achieve highly sensitive hydrogen sensing capacity at visible and near-infrared wavelengths in the Nanomaterials 2021, 11, 47 2 of 13 case of normal or angular illumination from the side of narrow groove [18]. Despite there being a variety of nanogratings described in previous reports, most studies have focused mainly on only one or two typical optical characteristics.…”
Section: Introductionmentioning
confidence: 99%